Influence of Frequency Conversion Regulation of Dense Baking Circulating Fan on Dehydration and Yellowing Characteristics and Stress Resistance of Tobacco Leaves - Chenglong HE; Yonghua LIU; Guanhui LI; Jiawei LUO; Zhengfa SHI; Ning HUANG; Xin JIN; Lingli XIE; Yuhang ZHAO; Zhijun CHENG; Kesu WEI (Guangdong nongye kexue)
【Objective】Exploring the effects of frequency conversion regulation of intensive baking circulating fans on the dehydration and yellowing characteristics of tobacco leaves and their stress tolerance during the baking process, it will provid theoretical and practical support for optimizing the frequency conversion regulation of intensive baking circulating fans, and improving the quality and economic benefits of tobacco drying in actual production.【Method】Using the middle leaves of 'Yunyan 87' as the material, a comparative analysis was conducted on the water loss characteristics, color parameters, pigment content, antixidant enzyme activity, MDA content, physical properties, and chemical composition of tobacco leaves after baking under the fixed high-frequency group (CK, frequency 50 Hz) and the variable frequency control group (T, frequency 35 Hz-40 Hz-45 Hz-40 Hz).【Result】The frequency conversion control of the intensive baking fan prolonged the yellowing and color fixing periods of tobacco leaves, shortened the dry gluten period, and extended the total baking time by 8 hours. The variable frequency control group lost water slower in the middle and late stages of yellowing and color fixing, and the moisture content of tobacco leaves was significantly higher than that of the fixed high-frequency group after 60-96 hours of baking, which was beneficial for the degradation of total chlorophyll and carotenoids. After baking, the total chlorophyll and carotenoids of the variable frequency control group were significantly lower than that of the fixed high-frequency group, reduced by 58.03% and 73.79%, respectively. The variable frequency control group has a relatively high activity of antixidant enzymes during the color fixation period, which is beneficial for clearing ROS during the baking process. The MDA content significantly decreased at 48-96 hours, with a decrease of 29.18% to 53.35%. The overall color change of variable frequency control group was uniform and the color was relatively bright. Analysis of tobacco leaves after baking revealed the variable frequency control group increased leaf width and single leaf mass by 10.63% and 27.5%, respectively, while reducing softness value by 9.92% and improving softness. The variable frequency control treatment of the fan promoted the decomposition of large molecular substances such as starch and protein. After baking, the content of total nitrogen, potassium, starch, and protein in the leaves of the variable frequency control group decreased by 4.70%, 5.70%, 3.94%, and 8.65% respectively, compared to the fixed high-frequency group, and the total sugar content increased by 4.01%. The sensory evaluation quality test showed that the sensory evaluation quality of tobacco leaves in the variable frequency control group was significantly better than that in the fixed high-frequency group.【Conclusion】Compared to fixed high-frequency baking, variable frequency control of fans is more conducive to the coordination of yellowing and dehydration of tobacco leaves, which can improve the stress tolerance of tobacco leaves during baking, promote the transformation of internal substances and the improvement of physical properties of tobacco leaves after baking, and enhance the quality and sensory evaluation of tobacco leaves after baking.